Odontoid fracture complicating ankylosing spondylitis - Ozgocmen, S; Ardicoglu, O (Stockton Press, 2000)
Patients with ankylosing spondylitis are prone to fractures. We describe a 32-year-old male patient with an odontoid fracture and anterior dislocation of C1 vertebra relative to C2 complicating ankylosing spondylitis. The importance and difficulties of the rehabilitation program are stressed. The role of magnetic resonance imaging and three-dimensional computerized tomography in diagnosis is emphasized.
Keywords: ankylosing spondylitis; odontoid fracture; rehabilitation; MRI